Analyzing factors affecting the technical efficiency of small-scale seaweed farms using a two-stage double bootstrap DEA approach. Issue 1 (2nd January 2023) - Orbeta, Marvin Louie G.; Digal, Larry N.; Astronomo, Ivi Jaquelyn T.; Balgos, Carol Q.; Placencia, Shemaiah Gail P.; Loquias, Melissa P.; Codog, Paolo Enrico
ABSTRACT: Low productivity in seaweed farms in the Philippines is due to issues ranging from lack of training, weather damage, and prevalence of pest and diseases. This study sampled 63 small-scale seaweed farmers in Ipil, Zamboanga Sibugay, as part of a development project. Technical Efficiency (TE) scores were calculated using the two-stage double bootstrap Data Envelopment Analysis (DEA) approach to investigate the causes of inefficiencies and external factors affecting small-scale production. Bias-corrected TE scores reveal that input use can be reduced by 55% to produce the same level of output, suggesting significant efficiency gaps. Factors such as primary occupation, number of farms, access to credit, farm location, and type of product sold had significant effect on technical efficiency. Extending government loan facilities to include seaweed farmers can lead to a reduction in inefficiency. Government initiatives to encourage seaweed farming, choosing the right farm location, and providing information can positively impact efficiency.